Synchrotron-based near ambient-pressure X-ray photoelectron spectroscopy and electrochemical studies of passivation behavior of N- and V-containing martensitic stainless steel. (15th April 2023) - Yue, Xiaoqi; Larsson, Alfred; Tang, Huajie; Grespi, Andrea; Scardamaglia, Mattia; Shavorskiy, Andrey; Krishnan, Anantha; Lundgren, Edvin; Pan, Jinshan
Abstract: Passivation behavior of a N- and V-containing martensite stainless steel was studied by synchrotron-based near ambient-pressure X-ray photoelectron spectroscopy, electrochemical analyses, and thermodynamic calculation. The passive film consists of Cr 3+, Fe (2, 3)+, and V (2, 3, 4)+ oxides as inner layer, and Cr 3+ and Fe 3+ hydroxides as outer layer. Austenitization at 1080 o C (rather than 1010 o C) and anodic polarization facilitate transformation of CrN to Cr2 O3 leading to further enrichment of Cr 3+ oxide in the passive film. Whereas higher Cl - concentration promotes film dissolution leading to higher level of point defects and higher fraction of remaining V oxides in the passive film. Highlights: Synchrotron-based NAPXPS allows for in-situ analysis of passive film with electrolyte on surface. The passive film consists of Cr 3+, Fe (2, 3)+, V (2, 3, 4)+ oxide layer and Cr 3+, Fe 3+ hydroxide layer. Austenitization at 1080 o C results in higher Cr in matrix and more Cr2 O3 and Cr(OH)3 in passive film. High Cl - content leads to high level of point defects and more remaining V oxides in the passive film. Cr nitride in surface layer can transform to Cr2 O3 in passive film at relatively high potential.